Implementasi teknologi papan informasi digital pada Masjid Al Bayan Kelurahan Limbungan Baru Kecamatan Rumbai Pesisir Kota Pekanbaru - Mochamad Susantok; Rizadi Sasmita Darwis; Memen Akbar (Unri Conference Series: Community Engagement, 2019)
Al Bayan Mosque as a centre for Islamic activities and the community has problems in the absence of facilities and infrastructure for massive and interesting information delivery to the public. This is evident when a house fire disaster occurs, the community's response to the collection of social assistance funds is not fast. Collection of assistance and assistance to victims over a period of one week after the disaster. This is one example of the incident as a source of information that needs to be conveyed to the community and congregation of the Al Bayan mosque. As a place for Islamic activities, supporting facilities are needed to have a wider impact on the community. One of them is the presence of digital information board technology as a more attractive means of delivering information by displaying infographics. This technology replaces the role of conventional bulletin boards which are very limited to displaying information and less attractive. This technology is capable of displaying information in the form of text, digital images and videos. In addition, by connecting to the internet network, this digital information board is also capable of displaying video streaming and the pages of a website. This technology is equipped with a minimum of low power systems that are connected to a TV LED via an HDMI port. The result from a survey of usability is 93.5% for efficiency, 91.6% for effectiveness, and 87.6% for satisfaction. From that factor, the mean result of usability is 90.6% or score 4.54 form scale 1-5. In addition to the implementation of the technology above, the dissemination of information through the official social media account of the mosque made its reach touch to millennial circles. That is as a medium of interactive communication between the wider community and mosque administrators as well as a medium for disseminating digital content information. Thus, the application of this technology can benefit the wider community in delivering interesting information through digital media.